Alkaline molten salt thermal treatment of mixed waste plastics for oil production: Insight into the effects of molten salt alkalinity and plastic molecular structure - Ren, Yang; Dai, Qiqi; He, Jing; Hu, Hongyun; Li, Xian; Li, Aijun; Zhang, Changbin; Yao, Hong (Fuel (Guildford), 2025)
[Display omitted] •Alkaline molten salt thermal treatment of plastics for oil production is studied.•Enhanced oil production yield is achieved with molten salts of higher alkalinity.•Polyolefins predominantly yield α-olefins through promoting β-scission reactions.•PVC and PS yield aromatics by promoting dehydrochlorination and aromatization.•Gas quality greatly improved with 99 % Cl capture and over 80 % H2 enrichment. Pyrolysis has emerged as the primary strategy for recycling waste plastics into oil. However, the low thermal conductivity of plastics results in inefficient heat transfer and extended residence times, which is unfavorable for oil production. Here, a novel method by using thermally stable alkaline molten salt as an effective medium to enhance heat transfer and thermal reaction was proposed. The oil yield exhibited a direct correlation with molten salt alkalinity. NaOH-Na2CO3 system achieved remarkable gas upgrading: >99 % chlorine immobilization coupled with alkali-mediated hydrogen enrichment (H2 ratio > 80 %), enabled by catalytic carbon-alkali interactions. Plastic molecular structures governed product selectivity during molten salt thermal treatment: polyolefins (PE/PP) predominantly yielded α-olefins through promoting β-scission reactions, while polyvinyl chloride (PVC) and polystyrene decomposition generated aromatic hydrocarbons (BTX, styrene) via enhancing dehydrochlorination and aromatization. In co-processing of mixed plastics, weak interactions existed between PE and PP during both conventional and molten salt conversions, with product distributions resembling linear combinations of individual pyrolysis results. PVC-PS blends exhibited significant cross-reactivity: HCl evolved from PVC decomposition engaged in secondary reactions with styrene (PS product). Primary radicals on PS chains post-scission drove depolymerization pathways, elevating ethylbenzene/α-methylstyrene formation at the expense of styrene monomers. Molten salt reduced PVC-PS cross-reactivity via chlorine capture and H-radical redistribution, increasing styrene monomer yields by 142 %. These findings facilitate the high-value recycling of mixed waste plastics for oil production.